Analisis Efektivitas Sistem Pengendalian Manajemen dalam Meningkatkan Kinerja Organisasi pada UMKM di Indonesia - Nala Cahyani Earlyana; Putri Nabilah; Desta Viananda; Alvino Oktavierdinand S; Tries Ellia Sandari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the effectiveness of management control systems (MCS) in improving organizational performance, particularly in MSMEs in Indonesia. Management control systems are an important instrument used by organizations to ensure that all activities run in accordance with established strategic objectives. In the context of increasingly complex global competition, organizations are required to have control systems that are not only administrative in nature, but also capable of supporting decision-making, increasing efficiency, and encouraging innovation. This study uses a descriptive qualitative approach with a literature study method. Data were obtained from various scientific journals relevant to the topic of management control systems and organizational performance. Data analysis techniques were carried out through the stages of data reduction, data presentation, and drawing conclusions to obtain a comprehensive understanding of the relationship between MCS and organizational performance. The results of the study indicate that an effective management control system can improve organizational performance through targeted strategic planning, efficient budget control, and continuous performance evaluation. In addition, the effectiveness of MCS is also influenced by supporting factors such as information technology, organizational culture, work motivation, and leadership. Modern approaches in MCS, such as levers of control, play a role in creating a balance between control and innovation. Thus, implementing an integrated and adaptive management control system is essential to sustainably improve organizational performance and address the dynamics of a constantly changing business environment